Duration from vine emergence to flowering suggests a longday or rate of change of photoperiod response in white yam (Dioscorea rotundata Poir) - Ile, E.I.; Craufurd, Peter Q.; Asiedu, Robert; Battey, N.H. (Elsevier, 2007)
The objective of this study was to quantify the effect of photoperiod on the duration from vine (shoot) emergence to flowering in white or Guinea yam (Dioscorea rotundata). The duration from vine emergence to flowering in two clonal varieties of yam (TDr 131 and TDr 99-9) was recorded at 10 different sowing dateslocations in Nigeria. Durations to flowering varied from 40 to >88 days. Mean daily temperature and photoperiod between vine emergence and flowering varied from 25 to 27◦ C and 13.1 to 13.4 h day−1 , respectively. Both clones had similar responses to temperature, with base and optimum temperatures of 12 and 25–27◦ C, respectively. Thermal durations to flowering were strongly related (r2> 0.75–0.83) to absolute photoperiod (h) at vine emergence as well as to rate of change of photoperiod (s day−1) at vine emergence. The response to absolute photoperiod suggests that white yams are quantitative LDPs, flowering sooner in long than short days. Yams also flowered earlier when the rate of change of photoperiod was positive but small, or was negative. It is suggested that yams may use a combination of photoperiod and rate of change in order to fine tune flowering time.